A Review of Galls on Ferns and Lycophytes. Issue 1 (15th December 2018) - Santos, Marcelo Guerra; Hanson, Paul; Maia, Valeria Cid; Mehltreter, Klaus
Abstract: Fern–insect interactions have not received the same attention as angiosperm–insect interactions have. It has even been stated that ferns may have very few interactions with animals because of their lack of flowers, fruits, and seeds. Consequently, for many decades fern–insect interactions have been overlooked and underestimated, especially for highly developed interactions such as those with gall-formers. The present work aims to review the galls of ferns and lycophytes worldwide, to provide an updated checklist including unpublished data and to estimate the global gall diversity of ferns and lycophytes. We recorded 93 host species, belonging to 41 genera. Galls were found in 20 fern families and one lycophyte family (Selaginellaceae). Most galls occur within the more derived ferns of the order Polypodiales, especially the fern families Polypodiaceae (21 host species), Dryopteridaceae (14 host species) and Athyriaceae (11 host species). Thirty-eight of the 133 gall morphotypes were induced by mites and 95 by insects of six orders (Coleoptera, Diptera, Hymenoptera, Lepidoptera, Thysanoptera, and Hemiptera). Among the insects, Cecidomyiidae (Diptera) caused most of the galls (35 morphotypes). So far, most galls have been reported from the Neotropical region (40 spp.) and Oriental region (28 spp.).